The Motivational Factors Questionnaire in the Korean EFL context: predicting group membership according to English proficiency and multilingual status. Issue 4 (8th August 2018) - Thompson, Amy S.; Lee, Junkyu
ABSTRACT: This study uses Ryan's Motivational Factors Questionnaire (MFQ) as a data collection tool to explore the motivational factors which distinguish groups of Korean university language learners based on English proficiency and degree of multilingualism. The data were analysed using Exploratory Factor Analysis (EFA), multivariate analysis of variance (MANOVA) and Discriminant Function Analysis (DFA). The results of the EFA highlighted both similarities and differences to the constructs underlying the MFQ according to Ryan. For example, the EFA of the current study showed Ryan's construct of 'ideal L2 self' splitting into two distinct factors: 'ideal L2 self – English for general future dreams' and 'ideal L2 self – cognitively activated imagery'. Ryan's 'instrumentality' construct also split into two factors. These splits highlight the need for more research to understand the sub-constructs that might occur in the psychological constructs of self . Using the results from the EFA, a MANOVA and subsequent DFA highlighted a range of factors relating to anxiety, cultural interest, attitudes towards English and the influence of the USA, which predicted group membership based on L2 English proficiency. Group membership based on multilingual status (i.e. intermediate or higher level knowledge of L2 English plus at least another second language) was predicted by factors relating to interest in foreign languages and public self-confidence in English. These results underscore the importance of examining participants' background information (language proficiency and multilingual status) in conjunction with exploring motivational and related variables.